Privacy and Anonymity in the Information Society – Challenges for the European Union - Ioannis A. Tsoukalas; Panagiotis D. Siozos (The Scientific World Journal)
Electronic information is challenging traditional views on property and privacy. The explosion of digital data, driven by novel web applications, social networking, and mobile devices makes data security and the protection of privacy increasingly difficult. Furthermore, biometric data and radiofrequency identification applications enable correlations that are able to trace our cultural, behavioral, and emotional states. The concept of privacy in the digital realm is transformed and emerges as one of the biggest risks facing today's Information Society. In this context, the European Union (EU) policy-making procedures strive to adapt to the pace of technological advancement. The EU needs to improve the existing legal frameworks for privacy and data protection. It needs to work towards a “privacy by education” approach for the empowerment of “privacy-literate” European digital citizens.